A profile study of 50 cases of liver abcess treated by percutaneous catheter drainage - Patel, Prakash Babubhai; Shah, Jignesh; Baria, Suyadeep (International Surgery Journal, 2017)
Background: Liver abscess is a life-threatening disease. Continuous catheter drainage is widely accepted and in combination with antibiotics is considered a safe and effective method of management of liver abscess. The objective of this study was to evaluate predisposing factors and incidence of liver abscess in various age group, sex, social economic study and its comparison with various studies and to evaluate morbidity, mortality and complication rates in patients of liver abscess treated either by percutaneous USG guided catheter drainage. Methods: This is an observational study of 50 patients with pigtail catheter drainage and needle aspiration in liver abscess treated during the period of May 2011 to December 2013 at New Civil Hospital, Surat. Results: In the present study majority of case [11 cases (22.5%)] were observed in the age group of 31-40 years. Male female ratio in our study was 8.2:1. Majority of Liver abscess cases [34 cases (68 %)] belongs to low socio-economic class. The commonest symptoms are pain and fever seen in 64% each. In the present study 100% success rate with no recurrence. None of the patients expired in the present study. Median hospital stay is 5 days with range from 2-25 days. Conclusions: Percutaneous pigtail catheter drainage is more effective in large liver abscess.